Estudo dos possíveis efeitos genotóxicos em trabalhadores de curtume expostos a substâncias químicas contendo cromo III em Teresina-PI - Amaral, Fabrício Pires de Moura do (2012)
Occupational exposure in tannery environments has been the subject of study and scientific research. Controversial information about the toxicity of chromium III and its relationship with the epidemiology of the tannery employees served as a subsidy for this research. The objective of this study was to evaluate the possible genotoxic and mutagenic effects of the exposure of tannery workers in Teresina (PI) to chemicals containing chromium III through the use of biomarkers of DNA and chromosomal damage. This was a cross-sectional, observational and quantitative study. Samples were taken from the mucosa, blood and urine of 43 tannery workers to analyze mucosal micronuclei (20 workers), lymphocytic micronuclei (30 workers), mucosal comet assays (20 workers), lymphocytic comet assay (43 workers) and chromosomal aberrations (30 workers); the level of urinary chromium was also measured (27 employees).The same analyses were carried out in non-exposed workers of the tannery environment for statistical comparison. In addition, personal health questionnaires were administered as recommended by the International Commission for Protection Against Environmental Mutagens and Carcinogens-ICPEMC with the aim of correlating their information with data obtained in the tests. The results indicated significant increases (p <0.05) in: the number (8.100 ± 3.905 vs 1.200 ± 1.609) and frequency (0.403 ± 0.060 vs. 0.1513 ± 0.04887) of mucosal micronuclei; the number (17.73 ± 9.44 vs 10.90 ± 7.092) and frequency (0.886 ± 0.472 vs 0.306 ± 0.202) of lymphocytic micronuclei; and the total (16.3 ± 3.38 vs 0.60 ± 0.16) and frequency (8.01 ± 1.82 vs 0.403 ± 0.09) of chromosomal aberrations (Student’s t test). There was a significant increase (ANOVA, p <0.05) for all types of damage and frequency of damage to the mucosal and lymphocytic COMET assay. Urine chromium levels was higher in exposed workers than in non-exposed workers (p <0.05) (1.108 ± 1.277 vs 0.089 ± 0.027).Pearson correlations between the level of chromium in the urine and genotoxic analyses indicated a strong positive correlation with the frequency of chromosomal aberrations (r = 0.841, p = 0.018) and frequency of lymphocytic micronuclei (r = 0.730, p <0.0001). It was concluded that the tannery workers are at risk of toxicity and genetic instability associated with occupational exposure to chemical mixtures containing chromium III.